(untitled) (Педагогіка вищої та середньої школи, 2009)
In the article a basic principle of adaptation of students of pedagogical specialities are examined to professional activity in educational establishments, and also opens up conformity to the law of process of professional adaptation of future teachers in the period of studies in higher pedagogical educational establishment.